2005
DOI: 10.1038/nature04296
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic pathway signatures in human cancers as a guide to targeted therapies

Abstract: The development of an oncogenic state is a complex process involving the accumulation of multiple independent mutations that lead to deregulation of cell signalling pathways central to the control of cell growth and cell fate. The ability to define cancer subtypes, recurrence of disease and response to specific therapies using DNA microarray-based gene expression signatures has been demonstrated in multiple studies. Various studies have also demonstrated the potential for using gene expression profiles for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
1,846
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,807 publications
(1,898 citation statements)
references
References 18 publications
44
1,846
1
7
Order By: Relevance
“…To evaluate the relationship between LAMC2 mRNA expression level and prognosis in NSCLC, we used three publicly available mRNA microarray data: the first cohort of 204 ADCs from Japanese National Cancer Center (JNCC set; HG-U133A Plus 2.0; GSE31210), 46 the second cohort of a mix of 63 ADCs and 75 SCCs from the Samsung Medical Center (SMC set; HG-U133A Plus 2.0; GSE8894), 47 and the third cohort of 59 ADCs and 52 SCCs from Duke University Medical Center (DUMC set; HG-U133A Plus 2.0; GSE3141). 48 Detailed methods were described in the Supplementary section. IHC in human NSCLC specimens.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the relationship between LAMC2 mRNA expression level and prognosis in NSCLC, we used three publicly available mRNA microarray data: the first cohort of 204 ADCs from Japanese National Cancer Center (JNCC set; HG-U133A Plus 2.0; GSE31210), 46 the second cohort of a mix of 63 ADCs and 75 SCCs from the Samsung Medical Center (SMC set; HG-U133A Plus 2.0; GSE8894), 47 and the third cohort of 59 ADCs and 52 SCCs from Duke University Medical Center (DUMC set; HG-U133A Plus 2.0; GSE3141). 48 Detailed methods were described in the Supplementary section. IHC in human NSCLC specimens.…”
Section: Methodsmentioning
confidence: 99%
“…This is driving the concept that, rather than describing cancers according to their site of origin and clinicopathological parameters, tumours might alternatively be classified in terms of the main pathways that drive tumour cell proliferation (eg PI3K-PTEN-mTOR-driven cancer, Wnt-driven cancer, etc.) [122][123][124]. However, molecular tools to measure activation of the signalling pathways in tumour [129].…”
Section: Cell Cycle Phase Analysis As a Predictor Of Therapeutic Respmentioning
confidence: 99%
“…When E2F3a was ectopically expressed in quiescent mouse fibroblasts (Black et al, 2005), only four of the genes found to be differentially expressed (PCNA, PTMA, MAD2L1 and Rrm2) were common to our lists. When E2F3a was overexpressed in primary mammary epithelial cells (Bild et al, 2006), only PCNA was common to our lists. These differences might reflect the different approaches used in these studies and that key genes controlled by E2F3 may depend on its cellular context.…”
Section: Role Of E2f3 Expression In Human Bladder and Prostate Cancermentioning
confidence: 99%